REVITALISASI PARTISIPASI MASYARAKAT DALAM GERAKAN LITERASI NASIONAL: STUDI PADA PROGRAM KAMPUNG LITERASI - Layli Hidayah (Jurnal Bidang Pendidikan Dasar, 2019)
In the implementation of literacy practice launched by the government, not all policy makers understand the culture of literacy. Due to the lack of understanding and participation by the community in the success of the literacy program, it is only considered as only limited to reading and writing. It has been proven from the fact in the society that not all community library are crowded by visitors. This is a qualitative descriptive study which is intnended to elaborate the community participation in literacy village. Based on the results of the research, it was found that the need for village government participation in the optimization of literacy programs.